2011
DOI: 10.1100/tsw.2011.71
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity ofArtocarpus heterophyllusLam. (Jack Fruit) Leaf Extracts: Remarkable Attenuations of Hyperglycemia and Hyperlipidemia in Streptozotocin-Diabetic Rats

Abstract: The present study examines the antioxidative, hypoglycemic, and hypolipidemic activities of Artocarpus heterophyllus (jack fruit) leaf extracts (JFEs). The 70% ethanol (JFEE), n-butanol (JFBE), water (JFWE), chloroform (JFCE), and ethyl acetate (JFEAE) extracts were obtained. Both JFEE and JFBE markedly scavenge diphenylpicrylhydrazyl radical and chelate Fe+2in vitro. A compound was isolated from JFBE and identified using 1D and 2D 1H- and 13C-NMR. The administration of JFEE or JFBE to streptozotocin (STZ)-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…In the current study, treatment of rats with TAM resulted in a 4-fold increase in TNF-α level. In accordance with our results, Omar et al reported that TAM administration to rats resulted in a significant increase in TNF-α level [34]. Additional support comes from the reports indicating that pathology of TAM-induced liver injury includes inflammation resembling that of alcoholic hepatitis [35].…”
Section: Effec On Tnfsupporting
confidence: 92%
“…In the current study, treatment of rats with TAM resulted in a 4-fold increase in TNF-α level. In accordance with our results, Omar et al reported that TAM administration to rats resulted in a significant increase in TNF-α level [34]. Additional support comes from the reports indicating that pathology of TAM-induced liver injury includes inflammation resembling that of alcoholic hepatitis [35].…”
Section: Effec On Tnfsupporting
confidence: 92%
“…Among these activities, the antioxidant actions of these polyphenols derived from Artocarpus species have been frequently reported in vivo and in vitro (Omar et al, 2011;Sidahmed et al, 2013). However, an evaluation of their effect on the respiratory burst of neutrophils has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, seeds can be used in the treatment for cooling tonic and pectorial, roots for diarrhea and fever, leaves for activating milk and vermifuge, and the latex mixing with vinegar for healing of abscesses, snakebite, and glandular swellings [13]. The jackfruit has been found to restrict the diseases, such as inflammation and diabetes mellitus because of the useful proanthocyanidin, flavonoid, and phenolic compounds [14,15].…”
Section: Introductionmentioning
confidence: 99%